PAPARAN ORGANOFOSFAT KRONIK SEBAGAI FAKTOR RISIKO GANGGUAN KOGNITIF BERDASARKAN KADAR PHOSPHORYLATED TAU SERUM - ni luh Putu Dirasandhi Semedi Putri; Anak Agung Ayu Putri Laksmidew; i made oka Adnyana (NEURONA, 2020)
CHRONIC ORGANOPHOSPHATE EXPOSURE AS A RISK FACTOR OF NEUROCOGNITIVE IMPAIRMENT THROUGH HIGH LEVEL OF PHOSPHORYLATED TAU SERUMABSTRACT      Introduction: Chronic organophosphate exposure is predicted related to decreased of neurocognitive function, but the mechanism is still unclear. One possible mechanism is abnormal tau protein metabolism as measured in the serum.  Aims: To measure the role of chronic organophosphate exposure causing neurocognitive impairment through high serum levels of phosphorylated tau protein (p-tau).Methods: This case control study was conducted in Penarukan Village, Tabanan, Balifrom July 2018 to January 2019. This study involved farmers aged 40-60 years who used organophosphates pesticide for at least the last 2 years and did not wear any personal protective equipment during pesticide use. Neurocognitive function was evaluated using Mini Cog Test. The level of p-tau was measured by taking a 2 mililiters of blood sample and analyzed using enzyme-linked immunosorbent assay (ELISA) method.Results: Sixty six(case = 33; control = 33) subjects were enrolled.Exposure to pesticides for ≥10 years had a higher risk for neurocognitive impairment than <10 years (odds ratio 16.675; 95% CI 4.626-60.105). The receiver operating characteristic (ROC) curve showed normal limit of serum p-tau protein level was 78.67ng /L. Serum p-tau protein level≥78.67ng/L increased the risk for neurocognitive impairment (Odds ratio 20.8; 95%CI2.524-171.440). The results of the path analysis found the strength of organophosphate exposure on neurocognitive function through high serum p-tau protein levels was 6.2%.Discussions: Chronic exposure to organophosphate increased the risk of neurocognitive impairment partially mediated by high level of serum p-tau protein.Keywords: chronic exposure, neurocognitive impairment,organophosphate,phosphorylated tau protein serum.ABSTRAKPendahuluan: Paparan organofosfat kronik diperkirakan berhubungan dengan penurunan fungsi kognitif, tetapi mekanismenya belum jelas. Salah satu mekanisme yang diprediksi berperan adalah gangguan metabolisme protein phosphorylated tau (p-tau) yang dapat diukur kadarnya dalam serum. Tujuan: Mengukur peranan paparan organofosfat kronik dalam meningkatkan risiko gangguan fungsi kognitif berdasarkan kadar p-tau serum.Metode: Penelitian ini merupakan studi kasus kontrol di Desa Penarukan, Tabanan, Bali pada bulan Juli 2018 hingga Januari 2019. Subjek adalah petani berusia 40-60 tahun yang menggunakan organofosfat minimal 2 tahun terakhir tanpa menggunakan alat pelindung diri. Fungsi kognitif diperiksa menggunakan tes Mini-Cog. Kadar p-tau serum diukur dengan mengambil 2mL sampel darah dan dianalisis dengan metode enzyme-linked immunosorbent assay (ELISA).Hasil: Penelitian ini melibatkan 66 subjek penelitian (33 kasus dan 33 kontrol). Paparan pestisida selama ≥10 tahun berisiko lebih tinggi mengalami gangguan fungsi kognitif dibandingkan dengan paparam <10 tahun (RO 16,675; IK 95% 4,626-60,105). Kurva ROC menunjukkan batas nilai normal kadar p-tau 78,67ng/L. Kadar serum p-tau ≥78,67ng/L meningkatkan risiko gangguan neurokognitif (RO 20,8; IK95% 2,524-171,440). Hasil analisis jalur kausal didapatkan kekuatan pengaruh paparan organofosfat terhadap fungsi kognitif melalui kadar protein p-tau serum yang tinggi sebesar 6,2%.Diskusi: Paparan organofosfat kronik meningkatkan risiko gangguan fungsi kognitif yang dimediasi secara parsial oleh kadar protein p-tau serum yang tinggi. Kata kunci: Gangguan kognitif, organofosfat, paparan kronik, protein p-tau serum